Life is what you make it find your own path to fulfillment - Buffet, Peter (New York Harmony Books, 2010)
Composer, musician, and philanthropist Peter Buffett, son of billionaire investor Warren Buffett, says that the only real inheritance handed down from his parents was a philosophy: Forge your own path in life. It is a creed that has allowed him to follow his own passions, establish his own identity, and reap his own successes. Today's society, Buffett posits, has begun to replace a work ethic, relishing what you do, with a wealth ethic, honoring the payoff instead of the process. Yet, by focusing more on substance and less on reward, we can open doors of opportunity and strive toward a greater sense of fulfillment. Our journey in life rarely follows a straight line but is often met with false starts, crises, and blunders. How we push through and persevere is where we begin to create the life of our dreams--from discovering our vocations, to living out our bliss, to giving back to others
Keywords: Buffett, Peter